What the IOM Report on Graduate Medical Education Means for Physician Assistants. Issue 2 (June 2015) - Cawley, James F.
Abstract : Abstract: Graduate medical education (GME) is funded by taxpayers through Medicare subsidies that pay for physician residency training, primarily to teaching hospitals. The Institute of Medicine (IOM) recently conducted a study of US GME and issued a series of recommendations for future policy reform. This commentary examines the major elements of proposed reforms for GME and offers analysis of those that may pertain specifically to physician assistant education now and in the future.